Measurement of K-mu 3(0) form factors - Lai, A; Marras, D; Bevan, A; Dosanjh, R; Gershon, T; Hay, B; Kalmus, G; Lazzeroni, C; Munday, D; Olaiya, E; Parker, M; White, T; et al. (2007)
This Letter reports on a new high precision measurement of the form factors of the KL → π± μ∓ νμ decay. The data sample of about 2.3 × 106 events was recorded in 1999 by the NA48 experiment at CERN. Studying the Dalitz plot density we measured a linear, λ+′ = (20.5 ± 2.2stat ± 2.4syst) × 10-3, and a quadratic, λ+″ = (2.6 ± 0.9stat ± 1.0syst) × 10-3 term in the power expansion of the vector form factor. No evidence was found for a second order term for the scalar form factor; the linear slope was determined to be λ0 = (9.5 ± 1.1stat ± 0.8syst) × 10-3. Using a linear fit our results were: λ+ = (26.7 ± 0.6stat ± 0.8syst) × 10-3 and λ0 = (11.7 ± 0.7stat ± 1.0syst) × 10-3. A pole fit of the form factors yields: mV = (905 ± 9stat ± 17syst)   MeV / c2 and mS = (1400 ± 46stat ± 53syst)   MeV / c2. © 2007 Elsevier B.V. All rights reserved.